Role and prevalence of impaired awareness of hypoglycaemia in ambulance service attendances to people who have had a severe hypoglycaemic emergency: a mixed-methods study. Issue 4 (24th April 2018) - Duncan, Edward A S; Fitzpatrick, David; Ikegwuonu, Theresa; Evans, Josie; Maxwell, Margaret
Abstract : Objectives: (1) To compare the experiences of people who are affected by diabetes-related hypoglycaemia and either do or do not require an emergency attendance and (2) to measure the prevalence of impaired awareness of hypoglycaemia in patients who are attended by an ambulance service due to a severe hypoglycaemic event. Design: A sequential mixed-methods study. Setting: A qualitative interview study was undertaken with 31 people with diabetes (types 1 and 2) resident in the central belt of Scotland. A national prevalence survey of 590 Scottish Ambulance Service patients who had recently experienced a severe hypoglycaemic emergency requiring ambulance clinicians attendance. Impaired awareness of hypoglycaemia was measured using two standardised measures. Results: Considerable differences in impaired awareness of hypoglycaemia were found in the experiences of participants who did or did not require the ambulance service to treat their severe hypoglycaemic events. Those who required an ambulance reported fewer warning signs and symptoms. The prevalence of impaired awareness of hypoglycaemia in ambulance service call-outs as assessed by two standardised measures was 53% and 60%, respectively. Conclusions: The prevalence of impaired awareness of hypoglycaemia among those who require an ambulance following a hypoglycaemic event is more than twice that found in the general population of people with diabetes. This may be because the experiences of impaired awareness in people who require an ambulance following a severe hypoglycaemic event differ to those who do not. This study provides important information to guide future prehospital clinical practice, and to develop and evaluate theoretically informed interventions. Improvements in prehospital care for this patient population could lead to global improvements in health outcomes and decreased service costs.